2023
DOI: 10.21037/qims-22-1024
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intermediate- and high-risk prostate cancer with biparametric magnetic resonance imaging: a systematic review and meta-analysis

Abstract: Background: This systematic review and meta-analysis evaluated the diagnostic performance of biparametric magnetic resonance imaging (bpMRI) for the detection of intermediate-and high-risk prostate cancer (IHPC).Methods: Two medical databases (PubMed and Web of Science) were systematically reviewed by 2 independent researchers. Studies published before March 15, 2022, that used bpMRI (i.e., T2-weighted images combined with diffusion-weighted imaging) to detect prostate cancer (PCa) were included. The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Recently, numerous studies have presented compelling evidence in this domain ( 28 ). The commercially available software provided at https://fuse-ai.de/prostatecarcinoma-ai has a comparable level of reliability to that of radiologists in detecting carcinomas, with a patient-level sensitivity of 0.86, which, in contrast, is inferior to our model’s sensitivity value of 0.94.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have presented compelling evidence in this domain ( 28 ). The commercially available software provided at https://fuse-ai.de/prostatecarcinoma-ai has a comparable level of reliability to that of radiologists in detecting carcinomas, with a patient-level sensitivity of 0.86, which, in contrast, is inferior to our model’s sensitivity value of 0.94.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that the diagnostic accuracy of using PI-RADS outperforms the traditional serum PSA test or digital rectal examination. Although using mpMRI imaging can mitigate the overdiagnosis of PCa, false-positive and false-negative results are often encountered in clinical practice ( 11 - 13 ). The use of mpMRI as a triage test prior to prostate biopsy remains controversial.…”
Section: Introductionmentioning
confidence: 99%